Role of Financial Development, Green Technology Innovation, and Macroeconomic Dynamics Toward Carbon Emissions in China: Analysis Based on Bootstrap ARDL Approach - Yang, Jiayu; Sun, Yunpeng; Sun, Huaping; Lau, Chi Keung Marco; Apergis, Nicholas; Zhang, Kun (Frontiers in Environmental Science, 2022)
This study focuses on determining the relationship between carbon emissions, financial development, population, green technology innovation, energy Consumption, and employment rate from 1980 to 2019 in China. The study applies the Unit-root test, Bootstrapped ARDL Co-integration and the Granger causality to examine the data properties and association between the variables of interest. Empirical findings indicate that green technology innovations and financial development play a major role in environmental protection, specifically in the long run. In contrast, energy consumption and employment rate are more vulnerable to protecting the natural environment in China. On the other side, the findings under short-run estimation do not support the role of green technology innovation in reducing environmental degradation. Based on the empirical findings, it is suggested that a strong financial system would help to achieve long-run sustainability and the emissions mitigating effects can be further strengthen by implementing green technologies across industries. In doing so, strict environmental regulations can regulate financial and traditional industrial sector in adoption of energy efficient technologies.